Hubungan antara usia dan riwayat abortus dengan kejadian plasenta previa Pada ibu bersalin - Hammimatus Zainiyah (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2019)
Jaundice can occur in any baby, eitherbecause of the lack of touch or massage so baby islazy to breastfed making the liver ability to processbilirubin decreased and eventually happenedjaundice. Based on the results of preliminarystudies in BPS Ayu, from 10 infants aged 3-7 days showed 3 babies (30%) did not havephysiological jaundice and 7 infants (70%) hadphysiological jaundice. The purpose of the studywas to analyze the correlation between babymassage with physiological jaundice in infants aged3-7 days at BPS Ayu Surabaya.This study uses an analytical correlation method with cross-sectional approach Collecting data using observation sheets,the data taken on all populations of infants aged 37 days at BPS Ayu Pakal Surabaya by 40respondents and samples taken 36 respondents. The results were analyzed using frequencydistributions using cross tabulation test and Lambda.The results showed that, most of who are massagedwell were 19 respondents (52.8%), most of who arenot jaundiced were 21 respondents (58.3%). Theanalysis Lambda shows that the results of ρ valuewas p value (0.002) <α (0.05) so that Ho is rejected,which means there is correlation between babymassage with pphysiological jaundice in infantsaged 3-7 days at BPS Ayu Surabaya. Expected tomidwifes, or health professionals give advice to mothers on the prevention and treatment theincident of jaundice, one of them is by teachingthe proper baby massage technique.